2014
DOI: 10.9790/6737-0152328
|View full text |Cite
|
Sign up to set email alerts
|

The founding principles of Sport for Development programmes in Zimbabwe and challenges impeding effective programme implementation

Abstract: This article reviews, discusses and analyses the founding principles that have motivated and inspired the formation of two major Sport for Development (SFD) initiatives with specific reference to circumstances in a developing country like Zimbabwe. The paper proceeds by analysing the numerous challenges which Zimbabwe has faced in her quest to implement Sport for Development initiatives with specific reference to the two major SFD initiatives i.e the Community Sport Development project (CSDP) and the Youth Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Orunaboka and Nwachukwu (2012) opined that school administrator and educational authorities have realized the benefits accruing from participation in sports programmes and they have not hesitated in including sporting activities (physical education) in their curriculum as a part of the learning experiences offered to the students. Nhamo and Magonde (2014) carried out a research in Zimbabwe titled, The founding principles of Sport for Development programmes in Zimbabwe and challenges impeding effective programme implementation in which it was opined that, understanding the concept of sport for development (SFD) requires a good understanding of two basic underlying concepts "Development" and "Sport" and how effective the combination and interplay of the two can be used as a tool to enhance human and social development. Furthermore, research has shown that, development through sport is an emergent area of importance in both academic and practical settings, and is seen as a vehicle to facilitate sustainable social and economic improvement in regions of the world targeted (MacIntosh, Spence, & McDonald n.d.).…”
Section: Concept Of Sports For Developmentmentioning
confidence: 99%
“…Orunaboka and Nwachukwu (2012) opined that school administrator and educational authorities have realized the benefits accruing from participation in sports programmes and they have not hesitated in including sporting activities (physical education) in their curriculum as a part of the learning experiences offered to the students. Nhamo and Magonde (2014) carried out a research in Zimbabwe titled, The founding principles of Sport for Development programmes in Zimbabwe and challenges impeding effective programme implementation in which it was opined that, understanding the concept of sport for development (SFD) requires a good understanding of two basic underlying concepts "Development" and "Sport" and how effective the combination and interplay of the two can be used as a tool to enhance human and social development. Furthermore, research has shown that, development through sport is an emergent area of importance in both academic and practical settings, and is seen as a vehicle to facilitate sustainable social and economic improvement in regions of the world targeted (MacIntosh, Spence, & McDonald n.d.).…”
Section: Concept Of Sports For Developmentmentioning
confidence: 99%